1998
DOI: 10.1016/s0082-0784(98)80477-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of flame speed with stretch in turbulent premixed methane/air flames

Abstract: IntroductionIn the flamelet approach of turbulent premixed combustion, the flames are modeled as a wrinkled surface whose propagation speed, termed the "displacement speed," is prescribed in terms of the local flow field and flame geometry [l]. Theoretical studies [2] suggest a linear relation between the flame speed and stretch for small values of stretch, where 5' : is the laminar flame speed, l i a = m 5~/ S i is the nondimensional stretch or the Karlovitz number, and M a = L/SF is the Markstein number. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
125
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 19 publications
31
125
0
Order By: Relevance
“…However, such simulations remain extremely expensive and are not yet feasible for parametric studies. Previous work has indicated that displacement speed statistics obtained from three-dimensional DNS with simplified chemistry [14][15][16][17][18][19][20][21][22] are in agreement with those obtained from two-dimensional DNS with complex chemistry [3][4][5][6][7][8][9][10][11][12][13]. In the present study, three-dimensional DNS with simplified chemistry is adopted in order to allow for an extensive parametric study without excessive computational cost.…”
Section: Mathematical Backgroundsupporting
confidence: 77%
See 1 more Smart Citation
“…However, such simulations remain extremely expensive and are not yet feasible for parametric studies. Previous work has indicated that displacement speed statistics obtained from three-dimensional DNS with simplified chemistry [14][15][16][17][18][19][20][21][22] are in agreement with those obtained from two-dimensional DNS with complex chemistry [3][4][5][6][7][8][9][10][11][12][13]. In the present study, three-dimensional DNS with simplified chemistry is adopted in order to allow for an extensive parametric study without excessive computational cost.…”
Section: Mathematical Backgroundsupporting
confidence: 77%
“…The displacement speed is defined as the speed at which the flame surface moves normal to itself with respect to an initially coincident material surface. Statistics of displacement speed for turbulent premixed flames have been studied extensively in previous work based on two-dimensional direct numerical simulations (DNS) with detailed chemistry [3][4][5][6][7][8][9][10][11][12][13] and on three-dimensional DNS with simplified chemistry [14][15][16][17][18][19][20][21][22]. These studies have looked at the effects of local strain rate and curvature effect on S d [13][14][15][16][17][18][19][20][21][22][23][24] and have included the influence of root-mean-square (rms) turbulent velocity fluctuation magnitude u and Lewis number Le [9,15,17,22] on these effects.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest work in this area investigated two-dimensional configurations using a detailed C1 mechanism [1,2,3,4]. Bell et al [5] produced the first simulation of a turbulent methane flame in three dimensions with moderate-fidelity kinetics using DRM-19, which 20 is a simplified mechanism derived from GRIMech 1.2.…”
mentioning
confidence: 99%
“…In general, the instantaneous flame stretch is both positive and negative as has been noted in many earlier studies (Rutland and Trouvé, 1993;Bray and Cant, 1991;Chen and Im, 1998;Nye et al, 1996;Renou et al, 1998;Kostiuk and Bray, 1993). However, these studies suggested that there is 50% or less probability for the flame stretch to be negative and this probability can be calculated by integrating the pdf shown in Fig. 14 from −∞ to 0.…”
Section: Flame Surface Density and Flame Stretchmentioning
confidence: 76%
“…The instantaneous flame stretch can be positive or negative; a positive value implies that the flame surface area increases due to the combined effects of turbulence and flame propagation and negative stretch suggests that the flame surface is compressed resulting in the loss of flame area per unit volume. Earlier numerical (Rutland and Trouvé, 1993;Bray and Cant, 1991;Chen and Im, 1998), experimental (Nye et al, 1996;Renou et al, 1998) and modelling (Kostiuk and Bray, 1993) studies have demonstrated that there is 20-50% probability for the flame stretch to be negative. In the view of RANS methodology the average value of the flame stretch, Φ s , is expected to be predominantly positive and many modelling methods have been proposed in the past with this view.…”
Section: Introductionmentioning
confidence: 98%